Prognostic value of morning surge of blood pressure in middle‐aged treated hypertensive patients. Issue 7 (21st June 2019) - Coccina, Francesca; Pierdomenico, Anna M.; Cuccurullo, Chiara; Vitulli, Piergiusto; Pizzicannella, Jacopo; Cipollone, Francesco; Pierdomenico, Sante D.
Abstract: We investigated the prognostic value of morning surge (MS) of blood pressure (BP) in middle‐aged treated hypertensive patients. The occurrence of a composite end point (coronary events, stroke, and heart failure requiring hospitalization) was evaluated in 1073 middle‐aged treated hypertensive patients (mean age 49 years). Patients with preawakening MS of BP above the 90th percentile (27/20.5 mm Hg for systolic/diastolic BP) were defined as having high MS of BP. During the follow‐up (mean 10.9 years), 131 cardiovascular events occurred. After adjustment for various covariates, including known risk markers and ambulatory BP parameters, patients with high MS of systolic BP (hazard ratio 1.81, 95% confidence interval 1.10‐2.96) and those with high MS of diastolic BP (hazard ratio 1.98, 95% confidence interval 1.19‐3.28) were at higher cardiovascular risk than those with normal MS. In middle‐aged treated hypertensive patients, high MS of systolic and diastolic BP is independently associated with increased cardiovascular risk.